Sound Effects in Polar Conditions - Roberts, Brian (Polar Record, 1944)
The impressive and all-pervading quietness following a fall of snow is a commonplace experience, though, so far as the writer is aware, only one set of measurements of the sound absorption of snow has been published. A cold spell in December 1938 provided a suitable opportunity to make such measurements in the reverberating chamber of the National Physical Laboratory at Teddington.